Research and implement of embedded wireless mobile communication system - TONG Xiao-nian1; AN Xing-ya2; LAN Xiao-pang3; WANG Jiang-qing1 (Tongxin xuebao)
In order to reduce hardware cost of embedded wireless mobile communication system and improve developing efficiency of embedded network protocol, the embedded wireless mobile communication terminal based on 8-bit basic MCU was proposed. Furthermore, according to software engineering principle, the general frame was designed to gener- ate embedded network protocol by UML state machine technology. The frame converted UML state figure into imple- menting codes of embedded network protocol. The experiment result shows that embedded wireless mobile communica- tion system not only reduces hardware expense but also incarnates standard and efficiency for development of embedded system software by UML state machine technology.